Saul Bellow - American Writers 65 : University of Minnesota Pamphlets on American Writers - Rovit, Earl H. (Book collections on Project MUSE., 1967)
Saul Bellow - American Writers 65 was first published in 1967. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.